FUNDAMENTAL CHARACTERISTICS OF THE NOTION OF HOMONYMY IN THE FIELD OF LINGUISTICS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article endeavors to explore the linguistic construct of homonymy, providing a comprehensive scrutiny of its fundamental characteristics, which include definitions, classifications, and its crucial role in the analysis of language.